2021
DOI: 10.1038/s41598-020-80943-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between olfactory dysfunction and cardiovascular disease and its risk factors in middle-aged and older adults

Abstract: While previous studies have reported olfactory dysfunction (OD) in relation to cardiovascular disease (CVD), few population-based studies have investigated whether such associations differ by sex. The purpose of this study was to identify the association between CVD and its risk factors with OD, and the sex-associated differences within the general population. We examined 20,016 adults aged 40 and older from the Korean National Health and Nutrition Examination Survey. All subjects reported on their history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…In the current study, the prevalence of asthma showed a significant increase in patients with OD (p < 0.001). Asthma and olfactory impairment have never been linked, according to a recent report published in 2021 by Rhyou et al 48 However, the presence of allergic rhinitis or sinusitis in association with asthma surely decreases the olfactory sensation. 29 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the prevalence of asthma showed a significant increase in patients with OD (p < 0.001). Asthma and olfactory impairment have never been linked, according to a recent report published in 2021 by Rhyou et al 48 However, the presence of allergic rhinitis or sinusitis in association with asthma surely decreases the olfactory sensation. 29 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…Olfactory loss and the risk of neurological disorders Olfactory loss accompanies 68 neurological disorders of which we are aware (Table 1). There are also other medical disorders that are accompanied by olfactory loss, such as diabetes, hypertension, cardiovascular disease, cancer, and obesity; disorders that may well have a neurological component (Bartoshuk, 1990;Liu et al, 2018;Zhang et al, 2019;Roh et al, 2021;Faour et al, 2022).…”
Section: Olfactory Loss Increases Neurological Riskmentioning
confidence: 99%
“…Coronary heart disease is associated with olfactory dysfunction ( Seubert et al, 2017 ), cardiovascular disease in general is more likely associated with olfactory dysfunction in men ( Roh et al, 2021 ), while alteration of smell and taste are prospectively associated with a larger increase in blood pressure ( Liu et al, 2018 ). It may be recalled that epithelial sodium channels participate in salty taste transduction but also in blood pressure regulation, like the olfactory receptors located in the kidney.…”
Section: Chemosensory Disturbances In Human Pathologymentioning
confidence: 99%